Aeroelastic model tests to study tall building vibration in boundary-layer and tornado winds. (15th March 2020) - Hou, Fangwei; Sarkar, Partha P.
Highlights: 3DOF-aeroelastic CAARC Tall Building model tests and aerodynamic damping assessment. Measurement and analysis of wind-induced building response in time domain. Comparison of tall building response in ABL Wind at three critical wind directions. Characterization of tall building response in stationary and translating tornadoes. Comparison of tall building response in ABL wind and tornado wind. Abstract: A three-degree-of-freedom aeroelastic model of the standard CAARC Tall Building with a rectangular cross section was tested in both atmospheric-boundary-layer (ABL) wind tunnel and tornado simulator to assess its susceptibility to wind-induced vibration in straight-line wind and tornado wind and compare the two responses. Time histories of acceleration at roof-height and mid-height of the model were measured at different wind speeds. The normalized response of the tall building model was obtained with respect to reduced velocities at critical angles of attack for the boundary-layer wind and at critical locations and orientations with respect to the tornado path. The aerodynamic damping of the tall building was identified from the measurements and validated with other tests; furthermore, the results were analyzed in both time-domain and frequency-domain to reveal the response characteristics. A comparison of the vibration response shows that the characteristics of the tornado-induced excitation are different and its magnitudes are much more severe from those of the conventional straight-line wind. The results obtained from this study can be used to validate both wind-tunnel and numerical methodologies used for assessing the wind-induced vibration of a tall building and will eventually help to develop guidelines to reduce the wind-induced damage or occupant discomfort as a result of excessive vibration.